ANALISIS KETERKAITAN KARAKTERISTIK DENGAN PENDAPATAN PENJUAL WEDANG JAHE (HIK) DI SURAKARTA - Supono, Boedyo (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2010)
ABSTRACT Hypothesis that is told (1) there are interrelationship wich significant characteristich with earnings of sellers gingers drink (HIK) in Surakarta (2) capital factor as one of most the bearing dominance with earning of sellers gingers drink (HIK) in Surakarta. Where as data analysis apply Chi Square test namely compare X2 calculate with X2 table. If X2 calculate bigger than X2 is table, Ha received by Ho rejected where as for knowing very factor dominant the bearing by comparing coefficient of contingency with maximum coefficient of contingency progressively tightly the bearing both variable. Interrelationship working capital with earning shown by level of X2 calculate = 4, 69 compared by X2 table = 9,49 so that Ho received. Location effort showing X2 calculate = 14,7 bigger from X2 table = 9,49 so that Ho rejected Ha is received, available to being concluded by location effort relating to earning of sellers gingers drink (HIK). Education with X2 calculate = 3,703 compared is smaller with X2 table = 9,49 so that Ho is received. Old effort yielding X2calculate = 0,374 smaller compared with X2 table = 9,49 hence Ho received. Where as X2 calculate of office hours = 3,398 is smaller if compared with X2 tabke = 9,49, thereby Hois received. Base upon coefficient of contingency compared with maximum coefficient of contingency hence location effort giving the biggest coefficient and closest with maximum coefficient of contingency, then hypothesis expressing anticipated by working capital factor as one of sellers characteristic gingers drink (HIK) in Surakarta is unprovable of the truth. Precisely research result indicate that location effort tightest of the bearing with earning of sellers gingers drink (HIK) in Surakarta. Keywords: characteristic of sellers gingers dringk (HIK), earning, interrelationship.